PENGARUH KEPERCAYAAN DIRI TERHADAP KEMATANGAN KARIR MAHASISWA PENDIDIKAN TEKNIK BANGUNAN - Desky Rohaeni, - (2022)
Career becomes one of the goals of individuals when they have completed the study period. Individuals are said to be mature in their careers if they are able to make career decisions. One of the factors that can increase career maturity is self-confidence. Self-confidence is an important part of the development of one's personality, namely as a determinant or driver of how a person behaves and behaves. The purpose of this study is to determine the description of self-confidence, career maturity and the influence of self-confidence on career maturity of students in Engineering Education. The method used in this study is the type of associative method with a quantitative approach. The measuring instrument of this research is using a questionnaire/questionnaire with a self-confidence scale referring to Lautser's (2003) theory and a career maturity scale referring to Super's theory. The population in this study was 72 students of Building Engineering Education class of 2018, the sampling technique used Purposive Sampling with considerations taken, namely students of 2018 Building Engineering Education who had taken industrial practice, PPLSP and property business courses. The samples taken were 52 students. Based on the results of the data analysis, it is obtained that the self-confidence picture is in the medium category of 40% and the career maturity picture in the very high category is 40%. According to the regression equation (Y ) = 28.980 + 0.419 X shows the coefficient number is positive, which means the greater the self-confidence, the better the career maturity of students. The regression significance test shows a significance value of 0.002 <0.05 and the results of Fcount 10.398 > Ftable 4.03 then the regression is significant and meaningful, meaning that Ha is accepted, that is, there is a significant effect of self-confidence on career maturity in Building Engineering Education students. Keywords: Confidence, Career Maturity, Decision, Student.